IBM z/OS V2R2 performance - Winnard, Keith (IBM Corporation, International Technical Support Organization, 2015)
This book will help familiarize you with the technical changes that were introduced into the performance areas with IBM z/OS V2R2. --
Number on resource description page: SG24829200. - "Z Systems.". - Includes bibliographical references. - Online resource; title from cover page (Safari, viewed January 22, 2016)
Keywords: z/OS; Database management; Bases de données; Gestion